IMPROVING LEARNING OUTCOMES IN ISLAMIC HISTORY LESSON BY USING VISUAL, AUDITORY AND KINESTHETIC (VAK) STRATEGIES - Mahmudi, Ihwan; Nisa, Salma Sholochatun; Setiyadi, Alif Cahya; Rokhayati, Siti (Abjadia : International Journal of Education, 2024)
This study addresses the teaching of Islamic History at Gontor Two for Girls, where traditional lecture methods have led to declining student engagement and performance. Specifically, the average initial score of class 3F students in the academic year 1443-1444 was 2.57, or 65%, indicating a need for improvement in learning outcomes. To address this issue, the study explores the effectiveness of the VAK (Visualization, Auditory, and Kinesthetics) Learning Strategy in enhancing student engagement and achievement. The research, conducted as Classroom Action Research following Kemmis & McTaggart’s model, involved planning, action, observation, and reflection over two cycles. The findings revealed that student activeness improved from 53% in the first cycle to 80% in the second cycle. Moreover, student learning outcomes saw significant improvement, with 37.14% of students meeting the average standard in the first cycle, increasing to 88.57% by the second cycle. Based on these results, the study recommends that students actively engage in lessons and that teachers adopt the VAK strategy, particularly for Islamic History subjects, to enhance both engagement and learning outcomes.